Elucidating the Origins of Subgap Tail States and Open‐Circuit Voltage in Methylammonium Lead Triiodide Perovskite Solar Cells. (25th June 2018) - Du, Tian; Kim, Jinhyun; Ngiam, Jonathan; Xu, Shengda; Barnes, Piers R. F.; Durrant, James R.; McLachlan, Martyn A.
Abstract: Recombination via subgap trap states is considered a limiting factor in the development of organometal halide perovskite solar cells. Here, the impact of active layer crystallinity on the accumulated charge and open‐circuit voltage ( V oc ) in solar cells based on methylammonium lead triiodide (CH3 NH3 PbI3, MAPI) is demonstrated. It is shown that MAPI crystallinity can be systematically tailored by modulating the stoichiometry of the precursor mix, where small quantities of excess methylammonium iodide (MAI) improve crystallinity, increasing device V oc by ≈200 mV. Using in situ differential charging and transient photovoltage measurements, charge density and charge carrier recombination lifetime are determined under operational conditions. Increased V oc is correlated to improved active layer crystallinity and a reduction in the density of trap states in MAPI. Photoluminescence spectroscopy shows that an increase in trap state density correlates with faster carrier trapping and more nonradiative recombination pathways. Fundamental insights into the origin of V oc in perovskite photovoltaics are provided and it is demonstrated why highly crystalline perovskite films are paramount for high‐performance devices. Abstract : A facile means of controlling crystallinity in methylammonium lead triiodide (MAPI) perovskite solar cells is outlined. Compositional modifications result in gains in open‐circuit voltage ( V oc ) of up to 200 mV, which also correlate with a reduction in trap states as crystallinity increases. Fundamental insights into the origin of V oc in perovskite photovoltaics are provided.